(untitled) (Tikrit Journal For Political Science, 2025)
The State of Israel faced many complex security challenges that required the country’s leaders to articulate basic principles of national security and formulate a national security strategy that for the first time outlined responses in accordance with the founding leader of the State of Israel, David Ben-Gurion. Its legitimacy has stood the test of time, while specific responses have been adapted and modified to meet Israel’s current and future challenges.